A short review on transition metal chalcogenides/carbon nanocomposites for energy storage. Issue 3 (1st September 2022) - Salarizadeh, Parisa; Rastgoo-Deylami, Mohadese; Askari, Mohammad Bagher; hooshyari, Khadijeh
Abstract: Introducing suitable electrode materials and electrolytes for supercapacitors and next-generation batteries should be considered for the industrial application of these devices. Among the proposed materials for them, transition metal chalcogenides (TMCs), are attractive and efficient options due to their unique properties such as appropriate layered structure, good oxidation state of transition metals, high thermal and mechanical stabilities, etc. However, applying other layered materials with high electrical conductivity e.g. carbon-based materials can lead to producing remarkable results for the mentioned applications. However, an interesting point is how making TMCs composite with different types of carbon materials leads to improve electrochemical and structural properties of TMCs as active materials. In the present short review, the structural and electrochemical improvements of different types of TMC composites with carbon-based materials and their mechanism are investigated for supercapacitors and next-generation rechargeable batteries.